An Analysis on the Second Year Students’ Difficulties in Comprehending Recount Text at SMPN 27 Padang - Umul Aiman; Fitrawati Fitrawati (Journal of English Language Teaching, 2019)
This research aimed to find out the students’ difficulties in comprehending recount texts viewed from the generic structure, social function and lexico grammatical features. This research is descriptive quantitative research. The sample of this research is 31 students selected using cluster random sampling. The instruments used in this research were reading test and interview. In reading test, the test consisted of 30 items multiple choice with five recount text related to generic structure, social functions and lexico grammatical features. The research data were in the form of interpretations of student test results and interviews with students. Based on data analysis, it was found that the students’ difficulties in comprehending recount texts were average. It was proved by 67,74%, students had difficulties in comprehending generic structure, 64,52% students had difficulties in comprehending social function, and 74,19% students had difficulties in comprehending lexico grammatical features. Furthermore, it was caused by lack of knowledge, limited vocabulary, less concentration and poor reading habit.